Patients' mouth opening as a factor for discomfort during maxillary buccal infiltration anesthesia: A randomized clinical trial and survey of opinion - Ahmad M El-Ma'aita; Ahmad A Madarati; Mohammad M Al-Rabab'ah; Mohammad M Hammad; Ibrahim Abu Tahun (Wolters Kluwer Medknow Publications, 2022)
Introduction: The aim of the study was to investigate (a) whether patients' mouth opening influenced their discomfort during maxillary buccal infiltration (MBI) anesthesia and (b) whether dentists preferred their patients' mouth opened during MBI or closed. Materials and Methods: The protocol of this study was registered in ClinicalTrials.gov (NCT03921190). In this parallel equivalence randomized clinical trial, 120 American Society of Anesthesiologists I or II adult patients with a maxillary posterior tooth diagnosed with irreversible pulpitis and normal apical tissues and scheduled for root canal treatment were included and randomly divided into two groups using a coin toss; Group A (n = 56) received MBI with an open mouth, while Group B (n = 64) were injected using a closed-mouth technique. Patients with psychological disorders, soft-tissue abnormalities, tenderness to palpation, or percussion, and those who used analgesics 12 h before the appointment were excluded. Patients rated their discomfort during needle penetration, cheek retraction, and their overall discomfort using a standard 100 mm visual analog scale (VAS). Furthermore, 50 practicing dentists assessed (on a standard 100 mm VAS) the visibility of the injection site and ease of cheek retraction during MBI using either technique and chose their preferred technique. Data were analyzed using the Student's t, independent sample t, and the Chi-square tests. Results: The mean discomfort experienced in Groups A and B were 32.4 and 31.6 upon needle penetration (P = 0.84), 28.9 and 18.9 upon cheek retraction (P < 0.001) and 32.6 and 25.0 throughout the injection procedure (P < 0.001), respectively. Out of 48 dentists who returned the completed forms, 38 dentists reported that they preferred the closed-mouth technique for MBI (P < 0.001). Conclusions: The closed-mouth technique of MBI anesthesia results in less patient discomfort and improved visibility.